Informed Traders, Intervention, and Price Leadership: A Deeper View of the Microstructure of the Foreign Exchange Market - Peiers, Bettina (Journal of Finance, 1997)
This article identifies price leadership patterns in foreign exchange trading, with a focus on central bank intervention as an informational trigger for leadership positioning. Granger causality tests applied to DM/US$ spot rate quotes reveal Deutsche Bank as a price leader up to 60 minutes prior to Bundesbank interventionary reports. By the minus 25-minute mark, interbank quote adjustments become two-way Granger-causal. These results suggest that central bank activity is revealed in stages: first to the price leader, then to competitors, and lastly to the general public.